International Council for Standardization in Haematology (ICSH) laboratory guidance for the evaluation of haemostasis analyser‐reagent test systems. Part 1: Instrument‐specific issues and commonly used coagulation screening tests. (29th November 2020) - Gardiner, Chris; Coleman, Robyn; de Maat, Moniek P. M.; Dorgalaleh, Akbar; Echenagucia, Marión; Gosselin, Robert C.; Ieko, Masahiro; Kitchen, Steve
Abstract: Before a new method is used for clinical testing, it is essential that it is evaluated for suitability for its intended purpose. This document gives guidance for the performance of verification, validation and implementation processes required by regulatory and accreditation bodies. It covers the planning and execution of an evaluation of the commonly performed screening tests (prothrombin time, activated partial thromboplastin time, thrombin time and fibrinogen assay), and instrument‐specific issues. Advice on selecting an appropriate haemostasis analyser, planning the evaluation, and assessing the reference, interval, precision, accuracy, and comparability of a haemostasis test system are also given. A second companion document will cover specialist haemostasis testing.